TRAJECTORY-TRACING AND CENTRALIZED CONTROL SYSTEMS FOR MAPPING TASKS USING MULTIPLE DRONES - Argiliana, Shania
Multiple drones can be used for mapping tasks, so high accuracy is needed in trajectory-tracing for mapping. In addition to accuracy, drones must complete their tasks in the shortest possible time. To achieve this, the drones will be controlled using a centralized control system connected to an access point. This control system treats each drone as a distinct individual, thus making the drones independent. Enhancing the accuracy of position tracing is done by detecting several square fiducial markers (SFM) in the positioning process. The position of the drone is assumed to be at the center of the camera, leading to more precise position calculations. Furthermore, a separation algorithm is also applied to the drones to avoid collisions while performing mapping tasks. This algorithm will separate the drones according to a predetermined safe distance, which is 200 cm. In this research, the number of drones used amounted to 2 drones. According to the research findings, the drones underwent a trajectory-tracing test along the x-axis and y-axis. Based on this test, the resulting RMSE value decreased. When the drones moved along the positive x-axis, the RMSE value obtained was 5,2 cm, lower than the previous research result of 19,3 cm. While performing mapping tasks, the drones traced the route and obtained RMSE values of 12,3 cm for drone A and 22,5 cm for drone B, with a travel time of 51 seconds. Thus, the technique of detecting multiple markers enhances the trajectory-tracing capability, and the drones can perform mapping tasks well even though they operate in a confined area of 5 m x 4 m.